The effect of floods on property value and house buyer awareness in Shah Alam - Omar Shariff, Alyaa Safia (2024)
This study looks into how floods affect the property values and how aware house buyers are of the problem. Shah Alam is a city that is growing quickly. It floods a lot, especially during the rainy season, which hurts the local housing market. Flooding is a big problem for the Shah Alam real estate market because it affects both property prices and people's choices about where to live. Even though people are trying to make these problems less of a problem, the complicated link between floods, property values, and buyer awareness is still not well known.These are the main objective is to identify the effect of floods on the housing property value in Shah Alam and to determine the awareness of house buyers in Shah Alam towards flood risk area. The study uses a mix of quantitative and qualitative methods, including a survey of 70 house buyers in Shah Alam and case studies for content analysis. The fact that 71.4% of people who answered the survey looked at flood risk maps before buying a home shows that they are very aware of the risks of flooding. Also, 70% knew that areas that might be good places to buy had been flooded in the past. More than half (48.6%) would talk to experts about the risks of flooding before buying a home in an area that is likely to flood. These results show that people who are interested in buying a home in Shah Alam know a lot about the risks of flooding and are taking steps to protect themselves. This could have an effect on future housing market trends and government policies.